Wpływ klęsk żywiołowych na rynek drzewny - Sikora, Adam (Leśne Prace Badawcze, 2017)
The aim of the study was to determine the impact an increased wood supply from the Beskid forests after natural disasters on the timber economy of the Węgierska Górka Forest District and its surroundings in the years 2004–2010. The analysis was based on the wood raw material sales recorded in the database of the State Forestry Information System (SILP). Information on the buyers’location and their main use for the raw material were obtained through the Central Statistical Office. Furthermore, wood material buyers were classified according to the Polish Classification of Activities (PCA) based on the year 2007, using only a subjective analysis designed for enterprises and other economic units in the national economy. Changes in sales of wood material to the selected buyer groups were investigated using statistical analyses of linear trends. A Pearson’s correlation analysis verified the relationships between the buyer groups and the supply of timber assortments by the Węgierska Górka Forest District. Other studies have also shown that an increased supply of raw material in the context of natural disasters affects the types of wood buyers and their location. In addition, they have shown an increase in interest towards the purchase of raw materials among buyers engaged in the wholesale trade of wood and other non-wood producers which in turn decrease the share purchased by sawmills.